PENGARUH KEDALAMAN TERHADAP PROSES PELAPISAN INTI BULAT PADA KERANG AIR TAWAR (ANODONTA WOODIANA) - Rachman, Boedi; Winanto, Tjahjo; Maskur, Maskur; Sukmajaya, Yade (Perhimpunan Biologi Indonesia, 2009)
ABSTRACTThe Effect of Depth to Deposition Process on Round Nucleus of Fresh Water Mussel (Anodontawoodiana). One of the affecting factors to the quality of pearl culture is the thickness of pearldepositions (nacre). The objective of this study was to obtain information on best level ofdepth to culture of pearl, to get fast nacre deposition and high quality of pearl. The researchwas conducted for 9 months, in the freshwater pond, was 300 m2 wide and 1 m deep. Freshwaterpearl Anodonta woodiana, sized ranging from 12 ? 15 cm were studied. Completely randomizeddesign was used with levels of deep treatment (A) 30 cm; (B) 60 cm and (C) 90 cm. The resultshowed that best thickness of pearl deposition by 90 cm deep (1.30 mm) but hasn?t biggestsignificant (P>0.05) to the deep of 60 cm (1.10 mm) and biggest significant (P< 0.05) to the deepof 30 cm (0.70 mm). The result of implantation was followed that 30, 60 and 90 cm deep were 11.9%; 12.2 %; 12.0 %, whereas survival rate was followed 79.2 %; 79 % and 78.7 %.Keywords: Freshwater mussel; Anodonta woodiana; effect; level of deepKata kunci: Kerang air tawar, Anodonta, woodiana, kedalaman laut